Design and manufacturing challenges of a microturbine wheel - Hosseini, Seyed Vahid; Gamil, Abdelaziz; Soodani, Sara; Nikolaidis, Theoklis; Madani, Seyed Hossein; Chen, Yong Kang; Chizari, Mahmoud (European Turbomachinery Society, 2023)
Micro gas turbine (MGT) is a core technology in many hybrid and integrated power systems to address the low-emission future aviation and decentralisation of energy generation. To achieve a high power-to-weight ratio as well as lowering the required maintenance, a new compact configuration with an air-bearing compartment was developed to build a 2 kW micro gas turbine. Designing a turbine wheel faced a multidisciplinary problem with many inputs and constraints in aerodynamic, heat transfer, strength, and manifesting aspects. To meet all requirements of these aspects, a design procedure is proposed in this paper. Since the manufacturing process affects the performance and life of the system, several processes, including casting, additive manufacturing (AM) and machining of the turbine wheel with different materials, were carried out, and the structural strength and performance of the components were investigated in this study. The prototype was tested experimentally to prove its performance and validate the concept. The cast wheel demonstrated both the required performance of 2 kW power output of the MGT in turbine inlet temperature of 1200 K and rotational speed of 170 krpm. However, the machined and additive manufactured samples for low-temperature/low-speed off-design conditions did not withstand structurally and called for a re-design or change in conditions.
Keywords: micro gas turbine; prototype; turbine wheel; additive manufacturing; casting; machining